Evaluation of US Orthopaedic Surgery Academic Centers Based on Measurements of Academic Achievement. Issue 3 (1st February 2019) - Namavar, Aram A.; Loftin, Amanda H.; Khahera, Anadjeet S.; Stavrakis, Alexandra I.; Hegde, Vishal; Johansen, Daniel; Zoller, Stephen; Bernthal, Nicholas
Abstract : Introduction: Although a variety of agencies have attempted to evaluate the academic achievements of orthopaedic surgery academic centers, most use opaque criteria that are difficult to interpret and do not provide clear targets for improvement. This study leverages a weighted algorithm using objective measurements that has been linked to academic achievement to attempt to provide a comprehensive assessment of scholarly accomplishment for orthopaedic surgery academic centers. Methods: We examined full-time faculty at 138 US orthopaedic surgery academic centers; part-time or volunteer faculty were excluded. Five metrics of academic achievement were assessed: National Institutes of Health funding (2013), number of publications, Hirschberg-index (ie, a metric of impact of publications), leadership positions held in orthopaedic surgery societies, and editorial board positions of top orthopaedic and subspecialty journals. Academic programs were given a score for every category, and the algorithm was used to calculate an overall score of academic achievement for each program. Results: The five most academically productive programs were Washington University in St. Louis, Hospital for Special Surgery, Mayo Clinic, University of Pennsylvania, and Thomas Jefferson University. Conclusion: This algorithm may provide faculty with an assessment tool that can establish benchmarks to help focus efforts toward increasing the academic productivity of their respective programs.